The Catch of the Hyperreal: Yossarian and the Ideological Vicissitudes of Hyperreality - Yazdizadeh, Abdolali (Text Matters: A Journal of Literature, Theory and Culture, 2018)
Hyperreality is a key term in Jean Baudrillard’s cultural theory, designating a phase in the development of image where it “masks the absence of a profound reality.” The ambiance of Joseph Heller’s Catch-22 (1961) closely corresponds to Baudrillard’s notion of the hyperreal as images persist to precede reality in the fictional world of the novel. Since for Baudrillard each order of simulacra produces a certain mode of ideological discourse that impacts the perception of reality, it is plausible that the characters of this fictional context should be ideologically impacted by the hyperreal discourse. From this vantage point it is possible to have a new critical assessment of Yossarian’s (protagonist) antiheroic stance and study the role of the “business of illusion,” whose ideological edifice is based on the discourse of the hyperreal, on his antiheroic stance and actions. By drawing on Baudrillard’s cultural theory this paper aims to read Heller’s novel as a postmodern allegory of rebellion against the hyperreality of the twentieth-century American life and trace its relevance to modern-day U.S.